Analisis Keterampilan Bertanya Siswa Kelas VIII pada Mata Pelajaran IPA - Afifah Naura Salamah; Erman Erman; Enny Susiyawati (UNIB Press, 2022)
This study aims to describe the quality of 8th grade students’ questioning skills in science subjects and the factors affecting it. This descriptive study with a quantitative approach involved 22 students of 8th grade students in an A-accredited school located in Waru District, Sidoarjo Regency. The instrument used was test and interview guidelines. The data collection techniques used was interviews and document analysis. Data analysis was done by grouping student questions based on cognitive level in Revised Bloom's Taxonomy. The results of the study showed that students' questioning skills at the cognitive level of C1 Remembering was 53.6%, C2 Understanding was 31%, C3 Applying was 7%, C4 Analyzing was 6.79%, C5 Evaluating was 2 %. As for the cognitive level of C6 Creating, it did not appear. Moreover, factors that influence the students' questioning skills were their interest in the texts, how important and close the text topics to the students' lives. In conclusion, the students' questioning skills were at low-level with interest in the text as the biggest influence on the students’ questions quality. The implication of this research is in learning, students should make high-level questions at C3 to C6 levels after reading science text.